2004
DOI: 10.1021/jp048827t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Carbon Nanofibers and Carbon Nanotubes through Methane Decomposition over Supported Cobalt Catalysts

Abstract: Catalytic performance of Co catalysts supported on different supports (MgO, Al2O3, SiO2, and TiO2) for the formation of carbon nanofibers through methane decomposition was investigated. Catalytic activity and the life of supported Co catalysts for methane decomposition at 773 K strongly depended on the type of catalytic supports; i.e., the catalytic performances of Co/Al2O3 and Co/MgO were superior to those of Co/TiO2 and Co/SiO2. All the Co catalysts produced carbon nanofibers with relatively uniform diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(113 citation statements)
references
References 43 publications
5
108
0
Order By: Relevance
“…At a temperature of 750°C and CH 4 pressure at 101 kPa, over the catalysts of Ni/SiO 2 , CuNi/SiO 2 , Rh-Ni/SiO 2 , Pd-Ni/SiO 2 , Ir-Ni/SiO 2 , Pt-Ni/SiO 2 , Pd/SiO 2 , Pd-Ni/Al 2 O 3 , Pd-Ni/TiO 2 , Pd-Ni/MgO and Pd-Ni/ CF (carbon fiber), it was found that the methane conversions were all below 15% [34]. At 500°C and CH 4 pressure of 101 kPa and catalysts of Co/SiO 2 , Co/TiO 2 , Co/MgO and Co/ Al 2 O 3 , the methane conversions were all below 10% [35]. Using the Ni-Cu/Al 2 O 3 catalyst, at 500°C, 600°C, 700°C and 750°C, the methane (undiluted) conversions were around 10%, 22%, 59%, and 65% respectively [36].…”
Section: Characterizationmentioning
confidence: 97%
“…At a temperature of 750°C and CH 4 pressure at 101 kPa, over the catalysts of Ni/SiO 2 , CuNi/SiO 2 , Rh-Ni/SiO 2 , Pd-Ni/SiO 2 , Ir-Ni/SiO 2 , Pt-Ni/SiO 2 , Pd/SiO 2 , Pd-Ni/Al 2 O 3 , Pd-Ni/TiO 2 , Pd-Ni/MgO and Pd-Ni/ CF (carbon fiber), it was found that the methane conversions were all below 15% [34]. At 500°C and CH 4 pressure of 101 kPa and catalysts of Co/SiO 2 , Co/TiO 2 , Co/MgO and Co/ Al 2 O 3 , the methane conversions were all below 10% [35]. Using the Ni-Cu/Al 2 O 3 catalyst, at 500°C, 600°C, 700°C and 750°C, the methane (undiluted) conversions were around 10%, 22%, 59%, and 65% respectively [36].…”
Section: Characterizationmentioning
confidence: 97%
“…The basic idea behind using a water soluble support returns to Steigerwalt and Lukehart [17] who employed silicate or carbonate. Metal catalysts, such as Fe [18][19][20][21], Ni [22,23], Cu [24], Co [25,26] and their alloys [27], have been investigated widely. However, until now, the reported catalysts require the lengthy process of reduction and calcination for their preparation [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Takenaka et al have recently investigated the effect of supports on CF formation for Co-based catalysts. 79 The Co/Al 2 O 3 and Co/ MgO catalysts were found to be superior to the Co/SiO 2 and the Co/TiO 2 catalysts for CF formation. Based on catalyst characterization studies the authors claimed that the 10-30 nm range for Co particles was preferred for CF formation.…”
Section: Production Of Carbon Filaments By Catalytic Methane Decomposmentioning
confidence: 91%
“…77 XANES studies showed that during the methane decomposition reaction the smaller sized Fe particles were transformed into Fe 3 C while the larger particles were converted into carbon atom saturated g-Fe species. The supports had a profound effect in determining the nature of the CF formed in the process; multi-walled CF and chain like carbon fibers were formed on Fe/Al 2 O 3 , while CF composed of spherical carbon units were formed along with chain like carbon fibers on Fe 2 O 3 /SiO 2 catalysts.…”
Section: Production Of Carbon Filaments By Catalytic Methane Decomposmentioning
confidence: 99%